The Influence Of Library Service Quality On Students’ Satisfaction At Smpn 1 Ulu Musi - Anugrahheni, Kitrang; Anggriani, Ida; Fitriano, Yun (Jurnal Pakar Manajemen, 2025)
Library services are developed through the utilization of library resources to meet the needs of users. The quality of library services can affect user satisfaction. If the needs of users are met, it will create satisfaction. The aim of this research is to find out the influence of service quality and trust on students’ satisfaction at Library SMPN 1 Ulu Musi. This type of research uses quantitative research. The analytical method in this research uses Validity Test, Reliability Test, Simple Linear Regression Analysis, Determination Coefficient, and hypothesis testing using t test and f test. The number of samples studied was 30 students of SMPN 1 Ulu Musi. From the results of linear regression analysis with a value of Y = 9.414 + 0.497 X. From the results of calculations using SPSS, the coefficient of determination value of R is 0.682. This means that the value of Variable (X) influences the variable (Y) by 68,2% while the remaining 31,8% is influenced by other variables not examined in this study.